BODIES DON’T JUST TELL STORIES, THEY TELL HISTORIES: Embodiment of Historical Trauma among American Indians and Alaska Natives() - Walters, Karina L. (Du Bois Rev, 2011)
Increasingly, understanding how the role of historical events and context affect present-day health inequities has become a dominant narrative among Native American communities. Historical trauma, which consists of traumatic events targeting a community (e.g., forced relocation) that cause catastrophic upheaval, has been posited by Native communities and some researchers to have pernicious effects that persist across generations through a myriad of mechanisms from biological to behavioral. Consistent with contemporary societal determinants of health approaches, the impact of historical trauma calls upon researchers to explicitly examine theoretically and empirically how historical processes and contexts become embodied. Scholarship that theoretically engages how historically traumatic events become embodied and affect the magnitude and distribution of health inequities is clearly needed. However, the scholarship on historical trauma is limited. Some scholars have focused on these events as etiological agents to social and psychological distress; others have focused on events as an outcome (e.g., historical trauma response); others still have focused on these events as mechanisms or pathwaysby which historical trauma is transmitted; and others have focused on historical trauma-related factors (e.g., collective loss) that interact with proximal stressors. These varied conceptualizations of historical trauma have hindered the ability to cogently theorize it and its impact on Native health. The purpose of this article is to explicate the link between historical trauma and the concept of embodiment. After an interdisciplinary review of the “state of the discipline,” we utilize ecosocial theory and the indigenist stress-coping model to argue that contemporary physical health reflects, in part, the embodiment of historical trauma. Future research directions are discussed.